Leadership crisis and decline in political confidence in (Israel) after the events of October 7, 2023: "An analysis of the reality and possible paths - Nizar Abdul Karim Hassan (Tikrit Journal For Political Science, 2026)
This research examines the Israeli leadership crisis following the events of October 7, 2023, by analyzing the conceptual framework of the crisis of leadership, trust, and political legitimacy, and linking it to the dysfunctions that afflicted the Israeli security and political system. The research focuses on the most prominent shifts in Israeli security doctrine through a comparison before and after the events, particularly the failure of deterrence, early warning, and rapid response systems. It also reviews the most significant manifestations of the crisis at both the internal and external levels, including declining public support, institutional divisions, and increasing international isolation. The research demonstrates that this crisis contributed to the erosion of political legitimacy and the loss of trust in leadership institutions, concluding that the events of October 7 constituted a structural turning point that threatened the stability of the Israeli political system.